"xdy-(3y+x^5y^{\\frac{1}{3}})dx=0\\\\\nxy'-3y=x^5y^{\\frac{1}{3}}"
Bernoulli equation
divisible by "y^{\\frac{1}{3}}"
"\\frac{xy'}{y^{\\frac{1}{3}}}-3y^\\frac{2}{3}=x^5"
we will replace
"y^{\\frac{2}{3}}=z(x)\\\\\ny=z^{\\frac{3}{2}}\\\\\ny'=\\frac{3}{2}z^{\\frac{1}{2}}z'\\\\\ny^{\\frac{1}{3}}=z^{\\frac{1}{2}}"
then
"\\frac{x\\cdot\\frac{3}{2}\\cdot z^{\\frac{1}{2}}\\cdot z'}{z^{\\frac{1}{2}}}-3z=x^5\\\\\n\\frac{3}{2}xz'-3z=x^5\\\\\n3xz'-6z=2x^5"
obtain a linear equation
1)
"3xz'-6z=0\\\\\n\\frac{dz}{z}=\\frac{2dx}{x}\\\\\nln|z|=2ln|x|+ln|C|\\\\\nz=C\\cdot x^2"
2)
"z=C(x)\\cdot x^2\\\\\nz'=C'x^2+2Cx\\\\"
substitute into the equation
"3xz'-6z=2x^5"
"3x(C'x^2+2Cx)-6Cx^2=2x^5\\\\\n3x^3C'-6x^2C-6Cx^2=2x^5\\\\\nC'=\\frac{2}{3}x^2\\\\\nC(x)=\\frac{2}{3}\\cdot\\frac{x^3}{3}+C_1"
Then
"z=(\\frac{2x^3}{9}+C_1)x^2\\\\\ny^{\\frac{2}{3}}=(\\frac{2x^3}{9}+C_1)x^2\\\\" is the general solution,
"y=0" is a solution
Comments
Leave a comment